Analisis Kelongsoran pada Tanah Lereng di Ruas Jalan Kecamatan Batu Ketulis sebagai Material Timbunan Jalan Ditinjau Terhadap Jenis Pemadatan dan Swelling - Kurniawan, Panca; iswan, iswan; Zakaria, Ahmad; Afriami, Lusmeilia (Universitas Lampung, 2022)
Batu Ketulis is a sub-district in the province of West Lampung. This regency is well-known as an advanced area in agriculture and other natural resources. Slopes can be formed naturally or man-made. In landfilling activities that will form a new slope will result in a change in stress in the soil which affects the stability of the soil.The purpose of this study was to determine the magnitude of the swelling on the slope soil in the Batu Ketulis road section of West Lampung Regency, to know the magnitude of the shear force on the slope soil as embankment material in the sub-district of batu ketulis roads, to know the stability of the slope as embankment material in the road section. the Batu Ketulis area so that the level of soil security can be identified . Soil conditions with fully saturated conditions have the least stability compared to other conditions. From the results of the analysis carried out on fully saturated soil conditions at locations 1 and 2 with variations in height and angle, the value of the critical safety factor is 1.262-1.282 with a height of 8 meters, an angle of 400 degrees.